2019
DOI: 10.1038/s41598-019-55825-0
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of live yeast based feed additive in early life promotes rumen microbial colonization and fibrolytic potential in lambs

Abstract: Rumen microbiota is of paramount importance for ruminant digestion efficiency as the microbial fermentations supply the host animal with essential sources of energy and nitrogen. Early separation of newborns from the dam and distribution of artificial milk (Artificial Milking System or AMS) could impair rumen microbial colonization, which would not only affect rumen function but also have possible negative effects on hindgut homeostasis, and impact animal health and performance. In this study, we monitored mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 69 publications
(80 reference statements)
4
22
0
1
Order By: Relevance
“…The difference between in vitro studies, our animal model, and these studies on conventional sheep may be attributable to differences in the broader ecology, where a newborn immature microbiota could be more ecologically favorable to the development of R. albus and R. flavefaciens , while a conventional adult microbiota may better favor F. succinogenes through unmeasured ecological interactions. This assumption agrees with studies of newborn calves and lambs in which cellulolytic ruminococci colonized the rumen earlier than F. succinogenes ( 33 , 34 ). Diet may also influence the composition of both the cellulolytic and broader community ( 32 , 35 37 ).…”
Section: Discussionsupporting
confidence: 90%
“…The difference between in vitro studies, our animal model, and these studies on conventional sheep may be attributable to differences in the broader ecology, where a newborn immature microbiota could be more ecologically favorable to the development of R. albus and R. flavefaciens , while a conventional adult microbiota may better favor F. succinogenes through unmeasured ecological interactions. This assumption agrees with studies of newborn calves and lambs in which cellulolytic ruminococci colonized the rumen earlier than F. succinogenes ( 33 , 34 ). Diet may also influence the composition of both the cellulolytic and broader community ( 32 , 35 37 ).…”
Section: Discussionsupporting
confidence: 90%
“…Stimulating lactic acid–utilizing bacteria could account for decreases in lactic acid concentrations induced by S. cerevisiae and the corresponding moderation of the rumen pH. The role of yeast is to stimulate lactate users, increase the number of lactate users, and serve as a competitor with lactate producers [ 8 ]. Moreover, it is interesting that the addition of LY increased ruminal pH ( p < 0.05), and it is in agreement with a previous study by Dias et al [ 35 ], who found that supplementing S. cerevisiae in the diet with high starch increased ruminal pH, whereas the concentration of lactate was reduced in lactating dairy cows.…”
Section: Resultsmentioning
confidence: 99%
“…S. cerevisiae has been used for many years, to promote ruminal fermentation, minimize the loss of energy and nutrients, and thus increase the ruminant production system. Some researchers have found that supplementation of the S. cerevisiae enhances ruminant digestion of feed in a variety of ways, such as increasing nutrient digestibility [ 6 ], maximizing the ruminal volatile fatty acid (VFA) proportion, decreasing ammonia nitrogen (NH 3 -N) [ 7 ], alleviating pH fluctuation, and stimulating the population of ruminal microorganisms [ 8 ]. High portions of concentrate in the ration significantly decreased the ruminal pH and NH 3 -N concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to fungi, protozoa were detected in the rumen of yaks after 1 month of age. A previous study detected protozoa in the rumen of lambs at approximately 21 days of age [ 42 ], which is earlier than that of yaks. In the present study, grazing yaks drank water from rivers or lakes instead of water troughs, which may preclude the colonization of rumen protozoa, as drinking water has been identified as a main source for rumen protozoa colonization [ 43 ].…”
Section: Discussionmentioning
confidence: 99%